2021
DOI: 10.1016/j.xkme.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy After SARS-CoV-2 Vaccination

Abstract: Here we present the first case of newly diagnosed IgA nephropathy (IgAN) after a SARS-CoV-2 vaccination. A 30-year-old man with no known past medical history presented with gross hematuria and subnephrotic proteinuria 24 hours after the second dose of the mRNA-1273 SARS-CoV-2 vaccine. A kidney biopsy showed IgAN. He was started on an angiotensin receptor blocker resulting in proteinuria reduction. Similar to natural infection of SARS-CoV2, persons who receive two mRNA-based vaccines demonstrate robust antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…36 articles were identified including a total of 49 reported cases (Table 1). These included MCD (n = 17) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), IgA nephropathy (IgAN) (n = 15) (26)(27)(28)(29)(30)(31)(32)(33)(34), IgA nephritis/vasculitis (n = 5) (10,30,35,36), ANCA glomerulonephritis/vasculitis (n = 5) (7,8,35,37,38), anti-GBM nephritis (n = 2) (28, 39), 1 case of each granulomatous vasculitis (40), acute tubulointerstitial nephritis (ATIN) (41), scleroderma renal crisis (42), IgG4-related disease nephritis (43), and primary MN (11).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…36 articles were identified including a total of 49 reported cases (Table 1). These included MCD (n = 17) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), IgA nephropathy (IgAN) (n = 15) (26)(27)(28)(29)(30)(31)(32)(33)(34), IgA nephritis/vasculitis (n = 5) (10,30,35,36), ANCA glomerulonephritis/vasculitis (n = 5) (7,8,35,37,38), anti-GBM nephritis (n = 2) (28, 39), 1 case of each granulomatous vasculitis (40), acute tubulointerstitial nephritis (ATIN) (41), scleroderma renal crisis (42), IgG4-related disease nephritis (43), and primary MN (11).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…They suggested that mRNA vaccines, similar to COVID-19 infection, produce strong antibodies against the RBD of the S1 protein. Therefore, the glycosylation of RBD and the immune response from the mRNA vaccine may be the underlying cause of the production of antibodies that resulted in the deposition of IgA immune-complexes in this patient (34). Moreover, severe COVID-19 infection is associated with a strong IgA response that may be triggered in the bronchial mucosa (55).…”
Section: Iga Nephropathymentioning
confidence: 91%
See 2 more Smart Citations
“…Huang et al report increased proteinuria and gross hematuria as a consequence of exacerbation of a patient's biopsy-proven IgAN concurrent with a COVID-19 infection [6]. Abramson et al report newly diagnosed IgAN in a kidney biopsy after a man presented with gross hematuria and proteinuria 24 hours after a COVID-19 vaccine [7]. In addition, there are two recent reports [8,9] of three patients with prior biopsy-proven IgAN presenting with gross hematuria usually with increased proteinuria within 24 hours of the second dose of SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%